2019
DOI: 10.3389/fneur.2018.01138
|View full text |Cite
|
Sign up to set email alerts
|

Visual Input Is the Main Trigger and Parametric Determinant for Catch-Up Saccades During Video Head Impulse Test in Bilateral Vestibular Loss

Abstract: Patients with vestibular deficit use slow eye movements or catch-up saccades (CUS) to compensate for impaired vestibulo-ocular reflex (VOR). The purpose of CUS is to bring the eyes back to the visual target. Covert CUS occur during high-velocity head rotation and overt CUS are generated after head rotation has stopped. Dynamic visual acuity is improved with an increased rate and gain of CUS. Nevertheless, the trigger and the parametric determinants of CUS are still under debate. To clarify the underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…As reported by numerous previous investigators [5,7,22,23,25,[57][58][59][60][61], we found that as the VOR loss increased compensatory saccade characteristics generally followed a similar pattern: the amplitude, frequency, and clustering increased while the latency became earlier (Fig 8). The rate of these changes to the reduction in VOR gain depended on both the visual condition and saccade number.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…As reported by numerous previous investigators [5,7,22,23,25,[57][58][59][60][61], we found that as the VOR loss increased compensatory saccade characteristics generally followed a similar pattern: the amplitude, frequency, and clustering increased while the latency became earlier (Fig 8). The rate of these changes to the reduction in VOR gain depended on both the visual condition and saccade number.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, after the bilateral loss of the compensatory velocity reflex in BVL, we found that subjects relied heavily in visual input-possibly either a position or velocity signal [54]-to generate the required position change, especially after the head stopped moving (Fig 1). Previous studies of compensatory saccades and posture after BVL also found an increased dependence on vision for position corrections [7,22,23,55]. Surprisingly, we found that in the horizontal plane a single bilaterally deafferented (BVD) subject could still regularly generate early saccades without visual fixation (Fig 1), supporting a proprioceptive trigger [26], although these saccades were much smaller in amplitude and scattered in latency.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…9 However, another study showed that there was no correlation between covert saccades and VOR gain. 27 In the patient group, our data showed that CS gain was negatively correlated with VOR gain and the correlation was strong, which suggested that the amplitude of combined CSs (overt and covert CSs) might be programmed based on residual VOR gain. In case of vestibular deficits, covert saccades have been proved to account for most eye displacement-compensating head movements and improved dynamic visual acuity, although they were not corrected with gaze position errors.…”
Section: Discussionmentioning
confidence: 60%